Forest Squier: capstone - Squier, Forest, artist (Colorado State University. Libraries, 2023)
The artist's statement: Throughout this semester I have become more and more intrigued with empty space, letting the paper just be as it is. There is something fascinating about emptiness, seeing past an object and into a world of the unknown. It exists in contradictions, it is beautiful, absurd, and terrifying, and yet it doesn’t exist at all. My work is inspired by my environment. I chose to use natural subjects like pine cones or flowers because they are things that I have encountered myself. Everything here is something that I have collected or observed. When I go outside I do not know what I will stumble upon and what will serve as inspiration. Most of my practice is informed by botanical illustration. It is methodical and rational– its main purpose being to depict a form with scientific accuracy. For me, there is an aim to being true to form, but also a relaxed intention. I approach my work through the practice of botanical illustration, but then I think of how to break the rules. The goal of my work is not to be viewed as tools for science but for dialogue between what we do and do not know.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: drawing